2014
DOI: 10.1109/tuffc.2014.2978
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of coupled-resonator filters using periodically slotted electrodes on FBARs [Correspondence]

Abstract: This paper discusses the use of periodically slotted top electrodes in the film bulk acoustic resonator (FBAR) structure for the realization of wideband coupled-resonator filters (CRFs), where evanescent modes in the periodic structure are used for the coupling between adjacent electrodes. First, wave propagation in this structure is investigated. Finite element analysis is performed for the Mo/ZnO/Mo structure. The result suggests that lateral wave propagation is controlled by the Bragg reflection, and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The authors showed that transverse modes experiencing propagation toward the crystal x direction can be suppressed by the use of free side boundaries (±x surfaces) in LN-based TSFBARs. 15,16,32) Thus, here we discuss only the plate wave propagation toward the y direction [see Fig. 1(a)].…”
Section: Transverse Modes Suppressionmentioning
confidence: 99%
“…The authors showed that transverse modes experiencing propagation toward the crystal x direction can be suppressed by the use of free side boundaries (±x surfaces) in LN-based TSFBARs. 15,16,32) Thus, here we discuss only the plate wave propagation toward the y direction [see Fig. 1(a)].…”
Section: Transverse Modes Suppressionmentioning
confidence: 99%
“…[8][9][10][11][12] In SAW devices, one of the most important design challenges is the suppression of transverse mode resonances. Various suppression techniques [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] have been proposed such as selective removal of SiO 2 , [17][18][19][20][21][22] bending resonator structure, 23) and piston mode design. [24][25][26][27][28] For the piston mode operation, phase shifters such as hammer head and metal dots are placed on electrodes near the aperture edges of interdigital transducer (IDT).…”
Section: Introductionmentioning
confidence: 99%
“…Liu, et al, proposed use of periodically slotted top electrodes for AlN-based TCRFs to increase the lateral coupling, and demonstrated their applicability to wideband TCRFs. 31) The authors applied this configuration to a LNbased TSBAR, and showed that a fractional bandwidth higher than 24% is achievable. 32) This paper is an extension of Ref.…”
Section: Introductionmentioning
confidence: 99%